Hollow Cathode and Low-Thrust Extraction Grid Analysis for a Miniature Ion Thruster. (3rd August 2008) - Wirz, Richard; Sullivan, Regina; Przybylowski, JoHanna; Silva, Mike
Abstract : Miniature ion thrusters are well suited for future space missions that require high efficiency, precision thrust, and low contamination in the mN to sub-mN range. JPL's miniature xenon Ion (MiXI) thruster has demonstrated an efficient discharge and ion extraction grid assembly using filament cathodes and the internal conduction (IC) cathode. JPL is currently preparing to incorporate a miniature hollow cathode for the MiXI discharge. Computational analyses anticipate that an axially upstream hollow cathode location provides the most favorable performance and beam profile; however, the hot surfaces of the hollow cathode must be sufficiently downstream to avoid demagnetization of the cathode magnet at the back of the chamber, which can significantly reduce discharge performance. MiXI's ion extraction grids are designed to provide> 3 mN of thrust; however, previous to this effort, the low-thrust characteristics had not been investigated. Experimental results obtained with the MiXI-II thruster (a near replica or the original MiXI thruster) show that sparse average discharge plasma densities of∼ 5 × 10 15 – 5 × 10 16   m - 3 allow the use of very low beamlet focusing extraction voltages of only∼ 250 –500 V, thus providing thrust levels as low as 0.03 mN for focused beamlet conditions. Consequently, the thrust range thus far demonstrated by MiXI in this and other tests is 0.03–1.54 mN.